Hall effects on flow of a Prandtl fluid through a porous medium in a planar channel with peristalsis - SHALINI, K. (International Journal of Psychosocial Rehabilitation, 2020)
in this paper, the effect of Hall on the flow of Prandtl fluid through a porous medium in a planar channel under the assumption of long wavelength is investigated. A Closed form solutions are obtained for axial velocity and pressure gradient. The effects of various emerging parameters on the pressure gradient, time averaged volume flow rate and frictional force are discussed with the aid of graphs.